The Effect Of Giving Kelakai Leaves (Stenocleana Palustri) To Increase Hb Levels In Anemia Adolescents At The Al Anwar Foundation, Karang Mulya Village, Pangkalan Banteng District, West Kotawaringin Regency - Natalia, Shanty; Watini (Universitas STRADA Indonesia, 2025)
One of the factor anemia in adolescents is due to lack intake of iron nutrition. the design of this study is quasi-experimental, pre-test and post test with control one group design. using purposive sampling technique on 30 respondents was obtained which will later be divided into 2 groups. The pusporse is to determine the relationship between the two variables. The results were obtained that the respondents in the experimental group of 14 respondents experienced mild anemia (93.33%), moderate anemia 1 person (6.67%), and the control group experienced mild anemia of 15 respondents (100%). Analysis using the Paired T test obtained the result of p = <0.000 which means that there is a relationship between giving kelakai leaves (STENOCLEANA PALUSTRI) to increase hb levels in anemia adolescents . Giving 100 grams of kelakai leaves in the form of soup is very effective in helping to increase HB levels in adolescents